(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objectives: This study aimed to use the Eating Attitudes Test-26 to determine the prevalence of eating-disorder risk and its associated factors among students at Nguyen Thi Minh Khai High School, Hanoi, in 2025. Subjects and methods: A cross-sectional study was conducted using a stratified random sampling method among high school students in Hanoi. Eating-disorder risk was assessed using the EAT-26 questionnaire. Results: The prevalence of students at risk of eating disorders was 13.4%. Several lifestyle-related factors were significantly associated with eating-disorder risk, including not regularly communicating with family (OR = 1.9; p < 0.05); Using the Internet at night for ≥ 2 hours/day (OR = 2.2; p < 0.05); Self-perceiving as overweight or obese (OR = 3.1; p < 0,01). In addition, BMI-for-age also showed a significant association. Students classified as overweight/obese had a higher risk compared with those with normal BMI (OR = 2.5; p < 0.05). Conclusion: Eating disorders are an important health issue among high school students and are associated with various psychosocial and nutritional factors. The findings highlight the need for early screening, psychological counseling, and school–family–based interventions to support healthy behaviors and protect adolescent well-being.